(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Objective The in vitro studies on phytochemical analysis and antioxidant activity of Heliotropium indicum Lin. (Boraginaceous) was evaluated by different assaying. Methods The in vitro antioxidant activity was evaluated for total antioxidant activity, 1,1-diphenylhydrazyl (DPPH) radical scavenging and hydroxyl radical scavenging activity. Results The percentage of inhibition of the total antioxidant activity, DPPH radical scavenging and hydroxyl radical scavenging activity was varying from ethanol and aqueous extracts. Conclusion The results clearly indicate that the ethanol and aqueous leaf extracts of the study species is effective in scavenging free radicals and has the potential to be a powerful antioxidant.